Erectile Function Outcomes after Robot‐Assisted Radical Prostatectomy: Is It Superior to Open Retropubic or Laparoscopic Approach?. Issue 1 (8th January 2014) - Isgoren, Abidin Egemen; Saitz, Theodore R.; Serefoglu, Ege Can
Abstract Introduction Erectile dysfunction (ED) is one of the most commonly affected domains of health‐related quality of life after prostate cancer therapy. Functional outcomes after radical prostatectomy (RP) have continued to improve through refinement of surgical techniques and development of several procedural modifications. In this context, it has been hypothesized that robotic technologies should simplify the preservation of the neurovascular bundle, thus possibly providing improved functional outcomes. Aim To compare the prevalence of post‐RP ED and identify whether recently developed robotic technologies are able to improve erectile function (EF) recovery after RP. Methods Literature Review. Main Outcome Measure To evaluate whether post‐therapy ED rates after robotic surgery have shown improvement when compared with the other forms of nerve‐sparing RP. Results Previously published series have shown EF recovery rates after robot‐assisted RP (RARP) ranging between 40% and 90% of patients at 12 months, postoperatively. Some claim that the RARP procedure can also significantly shorten recovery time in return of EF when compared with open RP. On the other hand, some authors have reported that patients undergoing minimally invasive RP have experienced even more ED on comparison. Conclusions Although it has been widely promoted by the industry and hospitals, at the moment there are not enough evidence‐based data to answer the question, "Does RARP surgery provide better EF outcomes?." Because of the current market trends and patient preferences, the perfect randomized study will probably never be performed, and thus the question of which procedure's results are superior will most likely remain unanswered. Isgoren AE, Saitz TR, and Serefoglu EC. Erectile function outcomes after robot‐assisted radical prostatectomy: Is it superior to open retropubic or laparoscopic approach? Sex Med Rev 2014;2:10–23.